THE IMPACT OF COVID-19 PANDEMIC ON ABSORPTION OF LABOR AND INCOME OF THE COFFEE SHOP IN MALANG CITY - Ida Nuraini; Izzatur Rochmaniyah (Universitas Muhammadiyah Kalimantan Timur, 2021)
The purpose of this study was to determine the real impact of the covid-19 pandemic on employment and income as well as the strategies taken by coffee shop owners in the Sudimoro coffee center, Malang City. The source of the data in this study was obtained from the owner of a coffee shop in the Sudimoro coffee center, Malang City. The population in this study were 57 coffee shops. The research sample was taken by census. The data analysis technique in this research is paired sample t-test and descriptive analysis The results showed that, based on the results of the different paired sample t-test, the following results were obtained: (1) there was a significant difference between quantity of labor absorbtion before the COVID-19 pandemic and during the COVID-19 pandemic, (2) there is a significant difference between income before the covid-19 pandemic and during the covid-19 pandemic, (3) the strategy taken by coffee shop owners to maintain their business is to promote through social media, serve online orders, innovate by changing the concept of the outlet from a coffee shop to a place for discussion and learning, so they must provide printers and storage for bags and books. Several coffee shops have changed the concept into a gathering place for various communities such as the Vespa community, the antique car community and other automotive communities.